The Factors Affecting The Efficiency of Continuous Ambulatory Peritoneal Dialysis in Children - Okdemir, Deniz; Cakar, Nilgun; Sahin, Irfan Oguz (Galenos Publ House, 2021)
Objective: Peritoneal dialysis is a complex and variable process. Many factors can affect efficiency of dialysis, and relevant mortality and morbidity rates. Efficient dialysis is important in improving quality of life as well as reducing the morbidity and mortality rates. Dialysis fill volume, intraperitoneal pressure and ultrafiltration (UF) are important variables that determine dialysis efficiency. We aimed to investigate the factors affecting dialysis efficiency and to determine necessities to develop a more effective dialysis program. Methods: Sixteen continuous ambulatory peritoneal dialysis (CAPD) patients between the ages of 7 and 19 years who were followed up in the Pediatric Nephrology Department were included in the study. Patients who had peritonitis, surgical or medical complications in the last 6 months were excluded from the study. Demographic data, duration of dialysis, hemogram, urea, creatinine, albumin, glucose levels, intraperitoneal pressures, peritoneal equilibration test (PET) and Kt/Vurea test results were recorded. Results: Mean Kt /Vurea, dialysis fill volume, UF, intraperitoneal pressure, Hb and serum albumin were found as 2.5 +/- 0.93 (1.224.64), 1123.4 +/- 126.86 (875-1360) ml/m2, 600.1 +/- 382.15 (85 -1375) ml, 12.9 +/- 2.77 (8.5-19) cm/H2O, 9.0 +/- 1.54 (6.3-11.8) gr/dl and 3.6 +/- 0.61 (2.45-4.8) gr/dl, respectively. A statistically significant relationship was shown between UF and Kt/Vurea (p=0.04). The mean duration of dialysis was 54 +/- 36 months. The majority of the cases had high (37.5%) and medium -high (31.25%) peritoneal permeability. High permeability was found to have a significant relationship with the duration of dialysis (p=0.04). Conclusion: Efficient peritoneal dialysis depends on preserved ultrafiltration. Therefore, the dialysate volume should be calculated according to the intraperitoneal pressure and dialysis should be adjusted according to the permeability properties of the peritoneal membrane.
Keywords: Dialysis efficiency; dialysis filling volume; intraperitoneal pressure; ultrafiltration